2018
DOI: 10.1111/jicd.12335
|View full text |Cite
|
Sign up to set email alerts
|

Oral Candida colonization and plaque type psoriasis: Is there any relationship?

Abstract: The prevalence of oral candidiasis is higher in psoriatic patients and is associated with disease severity. It is not exactly clear whether oral candidiasis can aggravate psoriasis or if psoriasis can predispose patients to oral candidiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(53 citation statements)
references
References 22 publications
8
44
1
Order By: Relevance
“…For example, rates were reported as 69% versus 44% for those without psoriasis in a study conducted in Jordan [28], and 47.2% versus 19.5% in a study conducted in Germany [29]. This trend was consistent with another study where patients with psoriasis receiving systemic treatment were excluded (20.0% versus 2.8%) [30]. The reason for this association is unclear.…”
Section: Epidemiology Of Candida Colonization and Infection In Psoriasissupporting
confidence: 63%
“…For example, rates were reported as 69% versus 44% for those without psoriasis in a study conducted in Jordan [28], and 47.2% versus 19.5% in a study conducted in Germany [29]. This trend was consistent with another study where patients with psoriasis receiving systemic treatment were excluded (20.0% versus 2.8%) [30]. The reason for this association is unclear.…”
Section: Epidemiology Of Candida Colonization and Infection In Psoriasissupporting
confidence: 63%
“…Therefore, the group of psoriasis patients was examined for a correlation between the prevalence of Candida and patients’ characteristics like age, gender, therapy and disease severity. Unlike previous studies, who did not observe a correlation between age and fungal colonisation, we found a substantially higher prevalence of C species in psoriasis patients and control subjects older than a median age of 51 years 13,20,21 . Consistent to previous examinations, we did not find any significant difference between the sexes 13,20,21 …”
Section: Discussionsupporting
confidence: 77%
“…For instances, a high rate of concomitant fungal infections was found in psoriatic nail patients (64,65) and enhanced Candida colonization was associated with more severe disease states (28). Further, Candida species detection rates for psoriatic patients have been shown to be significantly higher than in healthy individuals (29), especially in the oral mucosa (33,66,67). These observations together with our present data support the idea that fungal colonization and/or infection at various sites including the oral mucosa may predispose to psoriasis or amplify this disorder via systemic enrichment of fungal reactive Th17 cells.…”
Section: Discussionmentioning
confidence: 99%